Relationship between education and poverty in Nepal - Thapa, Surya Bahadur (Economic Journal of Development Issues, 2015)
Education is an important component of human resource development. It is the first most important determinant of income poverty. This paper aims to explore political economy of the country simply dealing with secondary data to produce the general statement relevant to the policy makers/ leaders of the country. In this context this paper tries to establish the linkage between income poverty and different levels of education. For this purpose secondary data published by United Nations Development Program and Central Bureau of Statistics were used. The descriptive findings based on these data provide fresh insights into some of the widely recognized perceptions on the extent and causes of educational deprivation of the poor that the level of educational attainment is a positive function of the levels of income. DOI: http://dx.doi.org/10.3126/ejdi.v15i1-2.11873 Economic Journal of Development Issues Vol. 15 & 16 No. 1-2, pp. 148-161